2020
DOI: 10.1111/sjop.12686
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying and cybervictimization among preadolescents: Does time perspective matter?

Abstract: Time perspective has been recognized as an important psychological dimension with a pervasive and powerful influence on human behavior. To the authors' knowledge, no studies have focused on the relationship between time perspective and cyberbullying behavior. The first aim of this research is to fill this gap by investigating the relationship between different time perspectives and both cyberbullying and cybervictimization among 6th to 8th grade students. The second objective was to investigate the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…These results are in line with previous research including high school graders (DeSmet et al, 2019;Kowalski et al, 2014). Moreover, middle school students' active involvement in CB perpetration was negatively correlated with future orientation (Longobardi et al, 2020). In this sense, school-based prevention efforts may benefit from focusing on students' future orientations to protect against involvement in CB (Nocentini et al, 2010).…”
Section: Findings/conclusion On Cb/cv and Psychosocial Variablessupporting
confidence: 90%
“…These results are in line with previous research including high school graders (DeSmet et al, 2019;Kowalski et al, 2014). Moreover, middle school students' active involvement in CB perpetration was negatively correlated with future orientation (Longobardi et al, 2020). In this sense, school-based prevention efforts may benefit from focusing on students' future orientations to protect against involvement in CB (Nocentini et al, 2010).…”
Section: Findings/conclusion On Cb/cv and Psychosocial Variablessupporting
confidence: 90%
“…Among this group of children, being a cybervictim implied higher scores in conduct problems and Externalizing problems (which, in addition to conduct problems, include hyperactivity/inattention problems). Prior studies had reported significant positive correlations between cybervictimization and externalizing symptoms as measured by the SDQ ( 28 ). Our study has confirmed this relationship in primary school children who do not suffer traditional bullying, although we cannot say whether these problems already occurred before suffering cyberbullying.…”
Section: Discussionmentioning
confidence: 98%
“…These results coincide with those found in other studies [ 88 , 89 , 90 ] that indicate that cybervictims and cyberbullies show less social competence. Other investigations that use the SDQ, developed by Sidera et al [ 49 ] and by Longobardi et al [ 37 ], confirm the relationship between being a victim of school cyberbullying and suffering emotional and behavioral problems. Through the SDQ, Kaiser et al [ 91 ] also found that cybervictims present more emotional and behavioral problems than non-victims, and that cyberbullies show greater prosocial behavior than victims.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, no research analyzing the relationship between profiles (victim or aggressor) evaluated using the ECIP-Q and other variables associated with cyberbullying has been found. Recent studies that use other questionnaires to evaluate cyberbullying show that both student victims [ 33 , 34 , 35 , 36 ] and aggressors [ 16 , 37 , 38 ] present symptoms of depression and antisocial behavior [ 39 ]. Some authors consider that school cyberbullying can generate a greater psychosocial maladjustment in the victims than that caused by face-to-face bullying [ 33 , 40 ] due to the aforementioned characteristics: large audience, anonymity of the bully, or the unlimited nature of the harassment [ 41 ].…”
Section: Introductionmentioning
confidence: 99%